System dynamics and auto-calibration framework for NSM model: Murrumbidgee River. (20th December 2007) - Elmahdi, Amgad; Malano, Hector; Etchells, Teri
Water sharing management is the major problem for water resources and irrigation management decision makers. However, irrigation systems are very complex and interconnected, posing significant difficulties in managing irrigation economically and environmentally. Therefore, it is imperative that innovative modelling approaches are employed to deal with the feedback loops inherent in these systems. Through the application of a system dynamics approach, a Network Simulation Model (NSM) was developed. The purpose of the NSM is to measure and identify the change in economic and environmental outputs of various allocations and demand scenarios. The aim of this study is to examine the use of two methods of auto calibration (single objective and multiobjective) over a variety of climatic and hydrological conditions. These methods have been compared and applied to three periods of calibration and validation using seven performance criteria. Results indicate that multiobjective method yields better identifiable parameters and an improved model structure